Development of the Oldenburg Epistemic Beliefs Questionnaire (OLEQ), a German Questionnaire Based on the Epistemic Belief Inventory (EBI) - Manuela Romana Paechter; Karin Rebmann; Tobias Schloemer; Bjoern Mokwinski; Yvonne Hanekamp; Martin Arendasy (Arizona State University, 2013)
The present research describes the development of a German questionnaire for measurement of domain-general epistemic beliefs.  Pre-studies on the psychometric properties of a German version of the Epistemic Beliefs Inventory (EBI) had emphasized the necessity to develop an instrument that is especially constructed for German-speaking samples. The new questionnaire, the Oldenburg Epistemic Beliefs Questionnaire (OLEQ), is based on the Epistemic Beliefs Inventory and includes original EBI items as well as newly developed ones.  The investigation of the psychometric properties of the questionnaire in a German-speaking sample showed a factor solution in which nearly all items loaded on the theoretically assumed dimensions.  The stability of the factor solution could be confirmed by means of confirmatory factor analysis in another sample.  Retest reliabilities of the different questionnaire dimensions were satisfactory.  The dimensions of the new instrument correlated significantly, yet to a moderate to weak degree, to the use of learning strategies.